2015
DOI: 10.16970/ted.63047
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance in two populations of Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) from Turkey

Abstract: SummaryIn this study, the resistance of two (Aydın and Urla) populations of T. absoluta against five commonly used insecticides (indoxacarb, spinosad, azadirachtin, chlorantraniliprole and metaflumizone) were determined. Further, the activity of insecticide detoxifying enzymes [gluthation-S-transferase (GST) and esterase (EST)] was also evaluated to confirm the resistance. Aydın population of T. absoluta had higher resistant values 8-fold, 3.79-fold, 6.4-fold and 1.84-fold for indoxacarb, metaflumizone, spinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Spinosad and abamectin show low LC50 values (<0.60 mg/L) and high slope values (>1.0). Similar LC50 values were obtained for abamectin in Turkey and Brazil (Siqueira et al, 2001; Silva et al, 2011, 2016b; Konuş, 2014; Barati et al, 2018) and for spinosad in Iran, Greece, Spain, Brazil, and Turkey (Campos et al, 2015a; Yalçin et al, 2015; Silva et al, 2016a; Roditakis et al, 2017a, 2018; Barati et al, 2018). The relatively lower expression of resistance against abamectin could be explained by the fact that this product is used at lower doses in the field, is typically used to control mites and is more rapidly degraded in the environment with low bioaccumulation (Clark et al, 1995).…”
Section: Discussionsupporting
confidence: 66%
“…Spinosad and abamectin show low LC50 values (<0.60 mg/L) and high slope values (>1.0). Similar LC50 values were obtained for abamectin in Turkey and Brazil (Siqueira et al, 2001; Silva et al, 2011, 2016b; Konuş, 2014; Barati et al, 2018) and for spinosad in Iran, Greece, Spain, Brazil, and Turkey (Campos et al, 2015a; Yalçin et al, 2015; Silva et al, 2016a; Roditakis et al, 2017a, 2018; Barati et al, 2018). The relatively lower expression of resistance against abamectin could be explained by the fact that this product is used at lower doses in the field, is typically used to control mites and is more rapidly degraded in the environment with low bioaccumulation (Clark et al, 1995).…”
Section: Discussionsupporting
confidence: 66%
“…Different letters above the means + SD bars indicate significant difference within the same bioassay according to Tukey test (p < 0.05) (2013) in three laboratories belonging to the three different countries, Greece, Italy, and Spain. In Turkey, the resistance of T. absoluta to five commonly used insecticides, spinosad, indoxacarb, metaflumizone, and chlorantraniliprole, was also recorded by Yalçin et al (2015). In the all three bioassays, the lowest LT 50 values were recorded by Metatech® WP, followed by Beauvitech® WP, Botanigard® ES and imidacloprid, respectively (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…1). The limited efficiency of imidacloprid could be due to the ability of T. absoluta to develop resistant strains to the frequently used synthetic insecticides (Yalçin et al 2015;Biondi et al 2018). Likewise, the resistance of T. absoluta to indoxacarb and chlorantraniliprole was detected by Roditakis et al Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Yalçın et al (2015) reported that T. absoluta populations obtained from the Aydın Province of Turkey had higher resistance; up to 8, 3.79 and 6.4 times for indoxacarb, metaflumizone and spinosad, respectively. Therefore, research on alternative methods for controlling this pest has become a necessity.…”
Section: Introductionmentioning
confidence: 99%